(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to identify the "effect of (Neale) model on reading comprehension among second grade intermediate students." To achieve the aim of the study, the researcher followed the experimental approach with partial control and the experimental design based on two groups, the experimental group and the control group, and the post-test. He randomly chose Division (A) to represent the experimental group that studies reading subjects using the (Neale) model, and Division (C) to represent the control group. Which studies reading topics in the usual way, and the research sample reached (64) students, by (33) students in the experimental group and (31) students in the control group. The researcher conducted statistical equivalence between the students of the two research groups in the following variables: (chronological age calculated in months, educational attainment of the parents, grades of the Arabic language for the second semester of the previous year, grades of linguistic ability test, and grades of the Raven test of intelligence), and they prepared a reading comprehension test consisting of ( 30) paragraphs, and the researcher studied the two research groups himself during the experiment period, which lasted (eight weeks of the first semester) for the academic year (2021-2022), and they used the following statistical methods (T-test for two independent samples, and square kay) ), Pearson’s correlation coefficient, difficulty and discrimination coefficient for the test items, the effectiveness of wrong alternatives, the Queder-Richardson equation (20) and the ETA equation. After analyzing the data statistically, the researcher concluded the following: " there difference with indication Statistic when Level (0.05) between Average grades students the group Experimental Whose are studying Using the Neale model style, and average grades students the group the officer Whose are studying the way Ordinary ".